An Analysis Of Multimodals On Grab Advertisement - Akmal Akmal; Chitra Latiffani; Iin Almeina (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
This study aims to analyse the grab advertisement by searching the form of audiovisual. This analysis of this study used the semiotic approach which was focused on the nultimodals system which included the linguistic, the visual, the audio, the gesture, and the spatial aspects. In the linguistic and the visual aspect, it used the theory of Cheong (2004). The results of this study described that the five multimodal systems were integrated each other especially in the contrast of colour. It was related to the metafunctions of the language, the material process of experiential function was so dominant (75,86%), In the interpersonal functions, the declarative was so dominant in used. In the textual functions, the marked theme is also dominant because they used the spoken language. The gesture aspect was good because they did not speak too much, but there were a few statements on the poster of the announcement.